พัฒนาการของการบริหารการพยาบาลในประเทศไทย - อรุณ นุรักษ์เข (จุฬาลงกรณ์มหาวิทยาลัย, 1978)
The purpose of this research was to study and analyse the development of nursing in Thailand, and to study the structure of nursing administration system in different periods, and to study the relationship between nursing service system and nursing education system. Research Procedures Basic data were collected through documentary and including previous research reports, thesis, reference materials, periodicals and other official documents. Major Finding Nursing education in Thailand was originated by Her Majesty, the late Queen Mother, in the reign of King Chulalongkorn. The School of Nursing was opened in 1896 under the control of the Department of Nursing and was financed by the Queen Mother. At that time the school was called School of Midwifery and Nursing, and now it became the Faculty of Nursing in Mahidol University. Nursing administration policy At the beginning, the purpose of nursing was to train women for the lack of proper care in maternity and infant welfare work. In 1914 the purpose turned toward public service and the war, so the school of nursing at Chulalongkorn hospital was established. In 1926, the purpose of nursing was to increase higher intellectual nurse. In 1937, the purpose of nursing was to be united, by established the nurses‘ association in the name of Nurses‘ association of Siam. It was the first women association in Thailand. After the second World War, the nursing administration emphasized in increasing number of nurses in order to serve the nations at this period. Nursing Organization In 1896, the nursing was under control of the Royal family. However, no central organization was set up to coordinates these works. In 1926, a complete reorganization of nursing was undertaken with the assistance of Rocky Fellor Foundation. Nowadays the nursing organization was under control of State University Bureau, Ministry of Public Health, Ministry of Defence, Ministry of Interior, and other privacy units. Personnel Administration Before 1926, administration power was directed by the Queen Mother advised by a group of appointed counselors. After the affiliated with the Rocky Feller Foundation. The administrative and hospital staffs connected with the organization of the school consist of the head of nursing division, an assistant to the head of nursing division, intructors, supervisors, head nurses and matron. Nursing Finance The financial supports were obtained from the Royal Funds, and later from the Rocky Feller Foundation, at present from the national budget and other special funds. Professional Preparation The preparation program in nursing administration started at the Graduate School, Chulalongkorn University in 1973. At present there were forty seven persons graduated from this school.